Personality profile of anaesthetists in a Department of Anaesthesiology - Segal, Craig (My University, 2017)
Background: Personality assessment has potential implications in anaesthesiology for recruitment into specialist programs, performance outcomes and identifying risk for burnout or psychological distress. The personality traits of anaesthetists can predispose them to occupational stress and burnout. Moreover, anaesthesiology is an inherently stressful workplace. Different researchers have found personality types to be prominent in subsets of doctors. The aim of this study was to describe the personality profile of the anaesthetists working in a department of Anaesthesiology. Methods: A descriptive, prospective, contextual study design was used. The Short Temperament-Character Inventory (TCI-140) is a self administered personality questionnaire and was used to describe the personality profile of anaesthetists. Results: Anaesthetists in the sample had low Novelty Seeking (median 25%), average Harm Avoidance (median 37%), average Reward Dependence (median 47%), high Persistence (median 70%), high Self Directness (median 87%), high Cooperativeness (median 73%) and average Self Transcendence (median 34%). Forty participants were classified as extreme temperament personality types. One participant was an immature personality type. Conclusions: : Male anaesthetists scored as low Harm Avoidance compared to average for female anaesthetists. There was no significant difference between anaesthetists of different ages. Senior anaesthetists scored low for Harm Avoidance and Self Transcendence compared to average for junior anaesthetists for those dimensions. The personality profile of anaesthetists in this sample is similar to other studies and reflects qualities required for the practice of anaesthesiology.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Masters of Medicine in the branch of Anaesthesiology Johannesburg 2017.
Keywords: Anesthetists